Research advances in surgically assisted rapid maxillary expansion - JIN Mengmeng; KANG Feiwu (Kouqiang hemian waike zazhi)
Surgically assisted rapid maxillary expansion (SARME) is a combined surgical-orthodontic treatment modality primarily used to address severe maxillary transverse deficiency (MTD) and dental arch constriction. SARME has undergone continuous refinement and optimization, becoming an essential therapeutic strategy in orthognathic treatment. This article comprehensively reviews the developmental trajectory of SARME, encompassing its surgical techniques, clinical efficacy, and potential complications. The review aims to provide clinicians and researchers with an updated perspective on SARME's evolving paradigm and propose future research directions.